Effect of calcination temperature on the performance of hydrothermally grown cerium dioxide (CeO2) nanorods for the removal of Congo red dyes - Rianjanu , Aditya; Nuraeni , Resti; Aflaha , Rizky; Khamidy , Nur Istiqomah; Triyana , Kuwat; Taher , Tarmizi (Greensusmater, 2024)
This study investigates the transformation of CeO2 nanostructures through various calcination temperatures and their subsequent impact on morphological, structural, and photocatalytic properties. X-ray diffraction (XRD) analysis reveals the presence of cerium oxycarbonate in the uncalcined samples, transitioning to a face centered cubic CeO2 phase post-calcination at 500°C. The scanning electron microscopy (SEM) imaging delineates a morphological evolution from distinct, rod-like structures in the uncalcined state to sintered, agglomerated forms as calcination temperatures ascend from 500°C to 800°C. The crystallite size, calculated using Scherrer's Equation, displayed a proportional increase with temperature. The photocatalytic degradation of Congo red dye under UV light was analyzed using UV-Vis spectroscopy, with the calcined samples exhibiting varying degrees of adsorption and photocatalytic activity. The study found that higher calcination temperatures correlate with increased photocatalytic performance, potentially due to enhanced crystallinity. This assertion is supported by pseudo-first-order kinetic modeling, indicating improved photocatalytic efficiency with higher calcination temperatures, underlined by increasing rate constants. These findings underscore the intricate relationship between calcination-induced morphological and structural changes and the photocatalytic prowess of CeO2 nanostructures.